Inovasi Pembelajaran Dengan Generative Learning dan Media Pop-Up Book: Pengaruhnya Terhadap Hasil Belajar Siswa Sekolah Dasar - Putu Linda Sasmitha Maharani; Ni Made Anggreni; I Komang Wisnu Budi Wijaya (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research is motivated by the low learning outcomes of students in Natural and Social Sciences (IPAS) subjects caused by the learning process that is still teacher-centered and the lack of use of innovative learning models and media. This study aims to analyze the influence of the Generative Learning learning model assisted by Pop-Up Book media on student learning outcomes on natural and artificial appearance materials in my area in grade III of SD Negeri 11 Sesetan City Denpasar Academic Year 2025/2026. This study uses a quantitative approach with a quasi experiment method and a Nonequivalent Control Group Design. The research population was all grade III students of SD Negeri 11 Sesetan with a sample of class III A as the experimental class and class III B as the control class. Data collection was carried out using learning outcome test instruments in the form of pretest and posttest. Data were analyzed using descriptive statistics and inferential statistics through normality tests, homogeneity tests, and hypothesis tests using independent sample t-tests. The results showed that there was a significant difference in learning outcomes between students who participated in learning using the Generative Learning model assisted by Pop-Up Book media and students who participated in conventional learning. The results of the hypothesis test showed a significance value (2-tailed) of 0.001 < 0.05, so that H? was rejected and H? was accepted. These findings show that the use of the Generative Learning model assisted by Pop-Up Book media can increase student involvement in learning and help students understand the concept of IPAS more concretely. Based on the results of the study, it can be concluded that the Generative Learning learning model assisted by Pop-Up Book media has a significant effect on the learning outcomes of social studies of grade III elementary school students. This research contributes as an alternative to innovative learning strategies that can help teachers create more active, interesting, and meaningful IPAS learning.